O beato do sertão de Canudos: Antônio Conselheiro como intelectual orgânico revolucionário - Silva, Leticia Queiroz (2025)
This study analyzes the trajectory and actions of Antônio Vicente Mendes Maciel, known as Antônio Conselheiro, through Antonio Gramsci‟s concept of the organic intellectual. The objective was to understand how his leadership, articulated through religious and political practices, contributed to the formation of the autonomous community of Belo Monte, in the Brazilian backlands, within the context of the Canudos War. The research utilized the manuscript Tempestades que se levantam no Coração de Maria (1897) as a primary source and conducted a critical analysis of the historiography on Canudos and its leader. Our hypothesis is that Conselheiro was a leader who, through religiosity, developed his political, critical, and conscious thinking about the way his people were treated by the authorities and the powerful. His actions mobilized marginalized workers around an alternative model of social organization based on solidarity and self-sufficiency. Furthermore, we believe that Antônio Vicente, as an organic intellectual, articulated religious, cultural, and political values, reaffirming his role as a leader of resistance and a symbol of the struggle against the structural inequalities of Brazilian society.